The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/cei.13283
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarkers for immunotherapy with ipilimumab in metastatic melanoma

Abstract: Summary New therapies, including the anti‐cytotoxic T lymphocyte antigen (CTLA)‐4 antibody, ipilimumab, is approved for metastatic melanoma. Prognostic biomarkers need to be identified, because the treatment has serious side effects. Serum samples were obtained before and during treatment from 56 patients with metastatic or unresectable malignant melanoma, receiving treatment with ipilimumab in a national Phase IV study (NCT0268196). Expression of a panel of 17 inflammatory‐related markers reflecting different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
1
26
0
1
Order By: Relevance
“…Simeone et al [ 68 ] reported the association of a decreased CRP level with disease stabilization and survival during 12 weeks of ipilimumab treatment in melanoma patients. These results have confirmation in the work of Nyakas et al [ 69 ], showing that increased CRP levels at several time points (baseline, week 4, and week 7) were observed in non-responders for ipilimumab therapy. Elevated pre-treatment CRP level was also shown to be related to poor OS in both anti-PD-1 and anti-CTLA-4 melanoma therapies [ 69 , 70 ].…”
Section: Predictive Biomarkers Related To the Host Immune Systemsupporting
confidence: 85%
“…Simeone et al [ 68 ] reported the association of a decreased CRP level with disease stabilization and survival during 12 weeks of ipilimumab treatment in melanoma patients. These results have confirmation in the work of Nyakas et al [ 69 ], showing that increased CRP levels at several time points (baseline, week 4, and week 7) were observed in non-responders for ipilimumab therapy. Elevated pre-treatment CRP level was also shown to be related to poor OS in both anti-PD-1 and anti-CTLA-4 melanoma therapies [ 69 , 70 ].…”
Section: Predictive Biomarkers Related To the Host Immune Systemsupporting
confidence: 85%
“…The released Galectin-3 can bind to components of extracellular matrix and its membrane counterparts of other cells, which have in a wide range of biological events including cellular homeostasis, immune function, angiogenesis, tumor invasion and metastasis 25 . Galectin-3 has been reported as a diagnostic or prognostic marker linked to metastasis in many types of cancer such as thyroid 26,27 , breast cancer 28 , melanoma 29 , lung cancer 30 , sarcoma 31 , gastric cancer 32 , prostate cancer 33 and oral tongue cancer 34 . Here, we showed that Galectin-3 was greatly expressed in highly metastatic NPC cells compared to lowly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 21 Altogether, some of these findings coincide with previous reports on the involvement of immunological proteins in antitumor response to CM. [22][23][24][25][26][27][28] Protein plasma levels can predict PFs To detect potential predictive biomarkers, we also analyzed the association between pre-trm plasma protein levels and PFS. No clinical variables were associated with PFS in the HiRIEF LC-MS/MS-analyzed subgroup of anti-PD-1 treatment cohort (n=13); therefore we performed univariate analyses, which showed associations between protein pre-trm plasma levels of 109 proteins and PFS in this cohort (p<0.05, no FDR; online supplementary table S8, additional file 2).…”
Section: Plasma Samples and Proteomesmentioning
confidence: 99%